2020
DOI: 10.24198/cropsaver.v3i2.29855
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Neem Seed Oil (Azadirachta indica) and Clove Leaf Oil (Syzygium aromaticum) Mixture on Cabbage Head Caterpillars (Crocidolomia pavonana)

Abstract: Crocidolomia pavonana is one of the important pest in Brassicaceae family. The used of botanical pesticides such as neem and clove can be used as alternative control for C. pavonana. This study aimed to examine the effect of neem oil, clove oil, and its mixture to C. pavonana. This experiment was conducted from November 2019 to May 2020 at the Laboratory Pesticides and Environmental Toxicology of the Department of Plant Pests and Diseases of the Faculty of Agriculture, Universitas Padjadjaran. The experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
1
2
0
1
Order By: Relevance
“…1). This was consistent with Ginasti et al, (2020) that reported the provision of clove leaf oil at 0.25% caused abnormal imagoes, characterized by curly wings and individuals that still has pupal skin attached to parts of the body. Clove leaf oil contains tannins compounds that act as stomach toxins, which can inhibit the activity of digestive enzymes so that insects lack nutrients.…”
Section: Growth and Development Activity Bioassaysupporting
confidence: 92%
See 1 more Smart Citation
“…1). This was consistent with Ginasti et al, (2020) that reported the provision of clove leaf oil at 0.25% caused abnormal imagoes, characterized by curly wings and individuals that still has pupal skin attached to parts of the body. Clove leaf oil contains tannins compounds that act as stomach toxins, which can inhibit the activity of digestive enzymes so that insects lack nutrients.…”
Section: Growth and Development Activity Bioassaysupporting
confidence: 92%
“…This was supported by Kaur et al (2021) who reported that the ratios of male to female insects of melon fly treated with neem oil, cedar oil and pongamia oil were lower than for the control, as neem oil, cedar oil and pongamia oil can be antifeedants, toxins, growth regulators and growth inhibitors against most plant pests. In addition, Ginasti et al (2020) stated that neem seed oil and clove leaf oil could reduce the number of adults that successfully matured.…”
Section: Growth and Development Activity Bioassaymentioning
confidence: 99%
“…Botanical insecticides from S. aromaticum contain compounds of eugenol, eugenyl acetate, ßcarophyllene methyl eugenol, and tannin [23,24,36]. Eugenol can poison by contact with nerve of Trichoplusia ni Hubner (Lepidoptera: Noctuidae) [5,8], while tannin act as stomach poison by inhibiting the activity of digestive enzymes of Crocidolomia pavonana F. (Lepidoptera: Crambidae) [24].…”
Section: Toxicity Of Plant Extracts Against Faw Larvaementioning
confidence: 99%
“…Kombinasi antara ekstrak daun P. indica dan C. odorata perlu dilakukan untuk memadukan senyawa metabolit sekunder di kedua tanaman tersebut. Hasil serupa diungkapkan oleh Ginasti et al (2020) bahwa kombinasi minyak biji mimba dan minyak daun teh konsentrasi 1 % merupakan perlakuan paling efektif terhadap mortalitas Crocidolomia pavonana, dengan nilai mortalitas sebesar 100%. Daun C. odorata dan P. indica memiliki kandungan senyawa aktif yang berperan terhadap mortalitas larva P. xylostella.…”
unclassified